2018
DOI: 10.1016/j.healun.2017.11.012
|View full text |Cite
|
Sign up to set email alerts
|

Induction regimen and survival in simultaneous heart-kidney transplant recipients

Abstract: r-ATG may provide a survival benefit in SHKT, especially in sensitized patients maintained on TAC/MPA/PRED at hospital discharge.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 43 publications
0
10
0
Order By: Relevance
“…If induction is to be used, the choice of agent for induction therapy needs to be personalized based on recipient's risk factors for infection, presence or absence of delayed graft function and recipient's immunologic profile 19 . For sensitized recipients and patients with delayed graft function, anti‐thymocyte globulin (ATG) induction can be considered 20 . For recipients with lower immunologic risk or at risk for infection, basiliximab induction can be considered.…”
Section: Results Of the Multidisciplinary Breakout Session Groupsmentioning
confidence: 99%
See 1 more Smart Citation
“…If induction is to be used, the choice of agent for induction therapy needs to be personalized based on recipient's risk factors for infection, presence or absence of delayed graft function and recipient's immunologic profile 19 . For sensitized recipients and patients with delayed graft function, anti‐thymocyte globulin (ATG) induction can be considered 20 . For recipients with lower immunologic risk or at risk for infection, basiliximab induction can be considered.…”
Section: Results Of the Multidisciplinary Breakout Session Groupsmentioning
confidence: 99%
“…19 For sensitized recipients and patients with delayed graft function, anti-thymocyte globulin (ATG) induction can be considered. 20 For recipients with lower immunologic risk or at risk for infection, basiliximab induction can be considered. Based on KT experience, the consensus from the nephrologists in the Heart/Kidney Workgroup was that calcineurin inhibitor (CNI) delay is not necessary for kidney protection.…”
Section: Managementmentioning
confidence: 99%
“…Recipients of rATG induction experienced similar patient survival (hazard ratio [HR] 0.81; 95% CI, 0.44–1.46; p = 0.48) as compared with no induction. However, when only sensitized patients were analyzed, survival was improved with rATG versus no induction (HR 0.19; 95% CI, 0.05–0.71; p < 0.001) 40 . The rates for infection requiring hospitalization for patients receiving rATG, IL2RA, and no induction were 45%, 50%, and 43% ( p = 0.28), respectively.…”
Section: Simultaneous Heart‐kidney Transplantationmentioning
confidence: 98%
“…In moderately sensitized patients (positive DSA and negative flow crossmatch), induction with ATG resulted in reduced occurrence of de novo DSA (dnDSA) and AMR compared to basiliximab [38]. In simultaneous heart and kidney transplants, sensitized patients (with PRA > 10%) treated with rATG induction had lower mortality [39]. Another randomized trial found a significantly reduced incidence as well as severity of acute rejection in high immunological risk patients, defined by Kidney Disease Improving Global Outcomes (KDIGO) as high number of MHC mismatches, younger recipient, older donor, PRA > 0%, presence of DSA, blood group incompatibility, DGF, and cold ischemic time > 24 h, treated with rATG versus basiliximab with acute rejection rates at 1 year (15% vs. 27%, p = 0.016) and 5 years (14% vs. 26%, p = 0.035) [37,40,41].…”
Section: Thymoglobulinmentioning
confidence: 99%